Pengaruh Pelatihan dan Pengalaman kerja terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Intervening - Fairuz Denaya Hafnidafitri; Azkia Nurfadilah; Linda Therecya Sianturi; Muhamad Satria Nur Hakim; Muhammad Zaky; Ni Nyoman Sawitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The study's overarching goal is to determine whether, and to what extent, employee motivation mediates the relationship between training and performance, as well as between performance and experience on the job and training, and between experience and performance on the job and work motivation. The material for this study came from a variety of online resources, including libraries, databases, and research tools like. Google Scholar, Mendeley, and open access e-journals and books. The results provide support for hypothesis H1, which states that training increases work motivation. Additionally, there is a positive and statistically significant effect of job experience on motivation, lending credence to hypothesis H2. Further evidence that motivation positively affects performance was uncovered, lending credence to hypothesis H3. Furthermore, both training and job experience have a positive and significant effect on performance, lending credence to hypotheses H4 and H5, respectively.